Enticing Investors : To Make a Serious Dent in Poverty, Africa Must Attract More Foreign Capital - World Bank (Washington, DC, 2012)
The nearly 750 million people who live in sub-Saharan Africa (SSA) are among the world's poorest. To foster the economic growth required to create jobs, raise living standards, and hasten development, SSA nations need to attract more foreign capital, which, by enhancing imported technology and the transfer of know-how, has proved instrumental in raising productivity in many countries.